Analysis of Human Decomposition Effect on DNA Quality with Short Tandem Repeats [STRS] Combined Index DNA System [CODIS] - Nily Sulistyorini, Ahmad Yudianto1 , Ma’rifatul Ula2 , Renny Sumino3 , Fery Setiawan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Personal identification is a problem in criminal or civil cases. Exact determination of personalidentity is very important in investigation as any error can be fatal in the judicial process. The process ofidentification that is often used is through DNA analysis. The problem that often becomes a serious problemfor both forensic DNA expert and other DNA expert is the condition of degraded DNA.Method and Materials: This study was conducted by analysing DNA damage patterns using CODIS STR(Short Tandem Repeat) markers to effect the decay process. The type of research used by experimentallaboratories, with research design used is time series.Results and Discussion: The result of DNA sample extraction from Psoas and Masseter muscle samplesshows the average minimum range of DNA levels for DNA typing is 0.25 ng with purity of 1.8 – 2(1). Theresult of this study prove the effect of decomposition on DNA concentration on each muscle. This study isalso showed a decrease in levels and purity in the samples of Psoas and Masseter muscle tissue buried in soil,sea/salt water and river/fresh water from day 1, 7, 14, 20 and 40.Conclusion: Psoas and Masseter muscle can be alternative material for forensic identification. The successof sequence mapping pattern from STR loci are TPOX, THO1, and CS1PO according to each GC content.GC content of THO1 and TPOX has the same relative value of 0,48, compared to CSF1PO value of 0,33.